Understanding mechanobiological and neuromechanical aspects of knee injuries - from modelling to rehabilitation - Wimmer, M.; Laube, W. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
Often knee injuries due to skiing accidents involve cartilage and/or ligamentous trauma. These injury types are a significant problem because they don't heal without intervention and can lead to cartilage degeneration and secondary osteoarthritis. In the case of anterior cruciate ligament (ACL) injury, disruption of the sensomotor system is another common complication, leading to functional deficits.